A review of the Glossogobius giuris complex in Australia, with wider discussion on nomenclature and possible synonymies - Hoese, Douglass F.; Hammer, Michael P. (Zootaxa, 2021)
Two species that had previously been referred to as Glossogobius giuris from Australia are redescribed and tentatively treated as Glossogobius giuris and Glossogobius laticeps. The two species are largely allopatric in Australia with G. laticeps found on the east coast of Queensland and some rivers of the Northern Territory, while G. giuris is distributed from the Northern Territory to rivers of the west coast of Western Australia. The two species are known to be genetically distinct and with some differences in colour patterns. Morphological features separating the species are minor and there is considerable overlap in many of the characters separating them. High variation in the Hammersley Ranges and Kimberley region of Western Australia further complicates separation of the species. The status of the Glossogobius giuris group from India is discussed as a key area to resolving an overall “giuris” species complex. Information is provided on the current identity of a number of species that had previously been considered synonyms of Glossogobius giuris. Extant types and difficulties assigning the types of known species are also discussed. A key is provided to aid identification of Australian species of Glossogobius.